Body mass index percentiles for rural Bengalee pre-school children aged 2-6 years, in comparison with the WHO reference and other studies - Das, Subal (Acta Biologica Szegediensis, 2012)
Objective: Compare the body mass index (BMI) percentiles of the rural Bengalee children with those in two recently developed international references: the WHO and the US Centers for Disease Control and Prevention (US CDC) growth references and two other studies. Design: A cross-sectional ethnic based survey. Setting: Thirty randomly selected villages, from rural areas of Purulia, Paschim Medinipur and Darjeeling. Subjects: 1,872 preschool children aged 2–6 years. Results: BMI percentiles were established using the LMS method, and were compared with the percentiles of the WHO reference, the US CDC reference and two other studies. BMI distributions and growth patterns in Bengalee preschool children were dramatically different from those in the two international reference populations. Compared with the international reference populations, rural Bengalee boys and girls (2-6 years) had substantially lower BMI percentiles than their counterparts in the reference populations. Conclusions: The present study described the different patterns of BMI values at the regional/ethnic level, and these values are useful as a reference for comparing different regions and for monitoring changes over time in Bengalee and children of Indian subcontinent. Higher proportions of children with extreme values in uni-directions indicate that Bengalee children currently facing an increasing level of undernutrition.